Proverbs 4:10–19 and the growing spate of Internet fraud amongst Nigerian youths - Uroko, Favour C. (Hervormde teologiese studies, 2021)
This research article examines the increasing spate of youths who engage in fraudulent Internet activities in Nigeria in the light of Proverbs 4:10–19. Nigerian youths are fast becoming impatient with their quest for wealth. This had led many of them to engage in high-level fraudulent Internet activities. It has come to a point where Internet fraudsters opened schools to teach prospecting youths how to make money fast. The circle keeps expanding on a daily basis. Their victims include the rich, the poor and unsuspecting foreigners. The study findings revealed that the spate of Internet fraud has continued to increase because more youths are willing to engage in such activities and other cybercrimes to make fast wealth, so that they can feel pride among other youths and the society. Proverbs 4:10–19 provide a lucid response to this sad development.ContributionIn the light of Proverbs 4:10–19, Nigerian youths are advised not to join evildoers because their path of wickedness ends in darkness and unhappiness.